An epidemiological study to assess unmet needs for family planning among married women in an urban slum area of Mumbai - Rawat, Shalini; Yadav, Ashwini; Gohar, Meraj (International Journal Of Community Medicine And Public Health, 2020)
Background: Unmet need is useful tool for monitoring family planning program and maternal health. Thus, reducing maternal mortality, unintended pregnancies and abortions. Use of modern contraceptives in 2017 prevented an estimated 308 million unintended pregnancies. Methods: A cross-sectional study was done among reproductive age (15-44 years) women attending general OPD in Urban health Training centre for a period of one month. Simple random sampling was used and sample size of 375 was taken. Data was analysed using SPSS software version 23. Results: Out of 375 women 85 (22.66%) were using contraceptives while 290 (77.34%) of women were not using any type of contraception. Total unmet need for spacing birth was 69 (18.4%) while for limiting birth was 98 (26.13%). Unmet need for spacing birth was highest 27 (26.21%) in age group of 20-25 years and unmet need for limiting birth was highest 10 (12.04%) in the age group of 30-35years. Educational status and socio-economic status of the women were found to be significantly associated with the unmet need. (50%) of women with no child and 24 (55.81%) women having one child had more need for spacing birth while women who had 2 children 26 (24.29%) had need for spacing and 41 (38.31%) had need for limiting births. Conclusions: The unmet need for contraception was found to be 44.53% which is much higher than the NFHS-4 data for urban Maharashtra i.e.11%. Appropriate measures should be taken for motivating couples to adopt the family planning methods specially among younger age women and economically backward groups